THE CONSEQUENCES OF RUSSIA’S ACCESSION TO WTO: CONCLUSIONS AND RECOMMENDATIONS - Kirsanov, Sergei; Safonov, Evgeny (European Scientific Journal, ESJ, 2014)
Actions of the Russian Government should include measures aimed at quick and painless restructuring of the competitive sectors of the Russian economy, and measures that can enhance the positive impact of membership in the world trade organization for joining WTO has brought the country to the maximum benefit at minimum losses. The main positive effect Russia’s accession to the world trade organization, you can call the General competitiveness of the economy, but in order for these changes to really influence the situation will take time. In the article the analysis of the situation faced by the industry and enterprises working in the WTO. There are recommendations for authorities. Participation in the WTO should pass with minimal losses for the Russian economy. Recommendations are aimed at reduction of costs and preferential development of competitive industries and enterprises, and to redirect those which cannot be competitive within the existing international division of labour.